2019
DOI: 10.1055/a-0959-0505
|View full text |Cite
|
Sign up to set email alerts
|

Bowel preparation for colonoscopy: European Society of Gastrointestinal Endoscopy (ESGE) Guideline – Update 2019

Abstract: Main RecommendationsESGE recommends a low fiber diet on the day preceding colonoscopy.Strong recommendation, moderate quality evidence.ESGE recommends the use of enhanced instructions for bowel preparation.Strong recommendation, moderate quality evidence.ESGE suggests adding oral simethicone to bowel preparation.Weak recommendation, moderate quality evidence.ESGE recommends split-dose bowel preparation for elective colonoscopy.Strong recommendation, high quality evidence.ESGE recommends, for patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
490
2
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(527 citation statements)
references
References 204 publications
(166 reference statements)
10
490
2
25
Order By: Relevance
“…Our results also revealed that simethicone with high or low dose had no signi cant difference of ADR and PDR, suggesting that the low-dose simethicone was not inferior to the high-dose one in terms of ADR and PDR, which is similar to the study of Li et al [39]. Although residual simethicone in biopsy channels could promote bio lm formation [40], simethicone adding to PEG solution could decrease the infection risk of endoscope-transmission [31].However, the optimal dose of SIM is yet to be ascertained [41]. Further research is required to determine the optimal dose of simethicone in clinical practice.…”
Section: Discussionsupporting
confidence: 73%
“…Our results also revealed that simethicone with high or low dose had no signi cant difference of ADR and PDR, suggesting that the low-dose simethicone was not inferior to the high-dose one in terms of ADR and PDR, which is similar to the study of Li et al [39]. Although residual simethicone in biopsy channels could promote bio lm formation [40], simethicone adding to PEG solution could decrease the infection risk of endoscope-transmission [31].However, the optimal dose of SIM is yet to be ascertained [41]. Further research is required to determine the optimal dose of simethicone in clinical practice.…”
Section: Discussionsupporting
confidence: 73%
“…Intestinal preparation plays an important role in colonoscopy and is the key to ensuring high-quality completion of colonoscopy. The 2019 European Digestive Endoscopy Society Guidelines for Intestinal Preparation [9] pointed out that poor bowel preparation could lead to poor bowel preparation. The detection rate of intestinal adenoma decreased, the failure rate of ileocecal bronchoscopy increased, the patient's pain increased, and the medical expenses were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of the various methods for bowel preparation, the rates of inadequate bowel preparation are recorded to be between 20% and 30% [15,16]. The European Society of Gastrointestinal Endoscopy Guideline in 2019 suggested that the minimum standard for adequate bowel preparation should not be less than 90% [7]. Therefore, it's necessary for us to improve the rates of adequate bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
“…than CLD in the quality of bowel preparation and has better tolerability [2][3][4][5]. Both the American Society for Gastrointestinal Endoscopy (ASGE) Guideline in 2015 and the European Society of Gastrointestinal Endoscopy (ESGE) Guideline in 2019 recommend LFD with FDA-approved purgatives for bowel preparation [6,7]. However, a LFD is considered as too restrictive to provide enough calories, leading to starvation, fatigue and hypoglycemia-induced side effects.…”
mentioning
confidence: 99%